Coexistence of open-angle glaucoma and sarcoidosis-associated optic neuropathy - Eun Hye Jung; Woonghee Kim; Ra Gyoung Yoon; Ko Eun Kim (BMC Ophthalmology, 2023)
Abstract Background In cases with advanced glaucomatous disc changes, further changes associated with other optic neuropathies cannot be easily identified. We present a case of preexisting open-angle glaucoma and concurrent involvement of sarcoidosis-associated optic neuropathy. Case presentation A 53-year-old man presented with gradual visual loss in his left eye, which began 1 year ago and accelerated 3 months ago. The best-corrected visual acuity in the right eye was 20/20 and counting fingers in the left. Intraocular pressures (IOP) were 12 mmHg in the right eye and 34 mmHg in the left. We diagnosed him with advanced open-angle glaucoma in the left eye based on the advanced glaucomatous cupping of the left optic disc. The IOP in the left eye dropped to 10 mmHg and was well controlled with antiglaucomatous medication; however, his left optic disc developed pallor 3 months after the treatment. The patient was revealed to be diagnosed with sarcoidosis a month ago and had been treated with systemic corticosteroids thereafter by a pulmonologist. Orbital magnetic resonance imaging revealed sarcoidosis-associated optic neuropathy in the left eye. Subsequently, optic neuropathy occurred in his right eye. Conclusions In eyes with advanced glaucomatous disc change, detecting the coexistence of other optic neuropathies can be difficult. This report highlights the importance of careful ophthalmic examinations and investigation for etiologies of other optic neuropathies if non-glaucomatous changes are suspected even in eyes with advanced glaucoma.